MENINGKATKAN HASIL BELAJAR MELALUI MULTIMEDIA GAME PDL BERBASIS MOBILE LEARNING BERBANTUAN PJBL DI SMP - Mokodompit, Aulia Vanisa (Universitas Tanjungpura, 2021)
Based on the results of interviews with teachers at SMP Negeri 1 Tilango, information was obtained that the value of mathematics learning achievement in class VIII on the pyramid material was still low and did not meet the KKM (Minimum Passing Grade Criteria) that had been determined. One of the causes of low learning achievement is the use of inappropriate media. This study aims to improve students' mathematics learning achievement through the multimedia game Adventure in Limas (PDL) based on mobile learning and the Project Based Learning (PBL) model. The subjects of this study were students of class VIII-1 of SMP Negeri 1 Tilango in the 2020/2021 even semester academic year with a total of 20 students. This research was conducted in two cycles. Data collectiontechniques in this study used teacher’s activity observation sheets, students’ activity observation sheets and written tests. The results of this study indicated that through mobile learning-based PDL multimedia games assisted by the PBL model, it can improve students' mathematics learning achievement in the Limas flat-sided space building material.